2003
DOI: 10.1128/jcm.41.10.4862-4864.2003
|View full text |Cite
|
Sign up to set email alerts
|

High Disease Burden of Diarrhea Due to Enterotoxigenic Escherichia coli among Rural Egyptian Infants and Young Children

Abstract: The incidence of enterotoxigenic Escherichia coli diarrhea among Egyptian children was 1.5 episodes per child per year and accounted for 66% of all first episodes of diarrhea after birth. The incidence increased from 1.7 episodes per child per year in the first 6 months of life to 2.3 in the second 6 months and declined thereafter.Enterotoxigenic Escherichia coli (ETEC) has been recognized as the most common cause of infectious diarrhea in infants and young children in developing countries (14). Manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 13 publications
10
79
1
4
Order By: Relevance
“…ETEC is estimated to cause 200 million cases of diarrhoea yearly, leading to 150,000 deaths [35]. Several countries in the world report ETEC as the most common cause of diarrhoea among all E. coli intestinal pathotypes, among them Bangladesh, Egypt and Mexico [36][37][38]. In addition, ETEC is known to be the most frequent cause of traveller's diarrhoea [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…ETEC is estimated to cause 200 million cases of diarrhoea yearly, leading to 150,000 deaths [35]. Several countries in the world report ETEC as the most common cause of diarrhoea among all E. coli intestinal pathotypes, among them Bangladesh, Egypt and Mexico [36][37][38]. In addition, ETEC is known to be the most frequent cause of traveller's diarrhoea [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Twofold serial dilutions of the culture filtrates were done in 96-well flat-bottom microtiter plates (Nunc, Roskilde, Denmark) (100 l per well; 12 wells per strain; dilutions from 1/2 to 1/2,048). A total of 20 l of the test filtrate containing 10 5 Vero cells in suspension were added to each well. The culture plates were incubated for 24 hours at 37C in a 5% CO 2 .…”
Section: Detection Of Vero Cytotoxin (Vt or Stx)mentioning
confidence: 99%
“…Globally diarrhoeal diseases account for almost a fifth of all deaths of children below five years of age, with an estimated 2.2 million deaths annually [2]. Epidemiological studies of diarrhoea have been reported from several African countries including South Africa [3], Gabon [4], Egypt [5] and Kenya [6]. A study conducted on travellers' diarrhoea that occurred in Europeans touring Mombasa, Kenya, reported an ETEC attack rate of 35% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Globally diarrhoeal diseases account for almost a fifth of all deaths of children below five years of age, with an estimated 2.2 million deaths annually [2]. Epidemiological studies of diarrhoea have been reported from several African countries including South Africa [3], Gabon [4], Egypt [5] and Kenya [6].…”
Section: Introductionmentioning
confidence: 99%